PENDIDIKAN SEKS ANAK USIA DINI DITINJAU DARI PERSPEKTIF ISLAM TK ISLAM AL-MUJAHIDDIN PEKANBARU - Putri Clawson; Rini Siska Yanti (P3M STKIP 'Aisyiyah Riau, 2019)
The background of this study is the lack of child shame when others see parts of their bodies, there are still children who are more likely to be close to friends of the opposite sex and the lack of understanding of teachers and parents in providing early childhood sex education. Data collection is done by conducting observations, interviews and documentation, and for this study using descriptive qualitative methods, namely explaining and describing the results of research, namely conducting direct research on children and teachers as samples in order to get a concrete picture of child sex education. Researchers also interviewed parents as additional data. The method used in this research is descriptive method, by collecting data, compiling data or classifying, analyzing and interpreting it. The results showed that teachers have played a role in providing sex education to children as informers at school. For example, good for children to imitate. And that in neatly dressed and clean Islam is part of the faith is also a habit of closing genitalia to avoid sexual harassment. However, parents of children have not fully provided sex education to children, as seen from the results of interviews that researchers have conducted that parents lack understanding of sex education, are still shy and rishi when delivering it to children.